2018
DOI: 10.1108/aa-10-2017-137
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and optimization of assembly precision-cost model based on 3D tolerance expression

Abstract: Purpose This paper aims to comprehensively achieve the requirements of high assembly precision and low cost, a precision-cost model of assembly based on three-dimensional (3D) tolerance is established in this paper. Design/methodology/approach The assembly precision is related to the tolerance of parts and the deformation of matching surfaces under load. In this paper, the small displacement torsor (SDT) theory is first utilized to analyze the manufacturing tolerances of parts and the assembly deformation de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…The tolerance of the closed-loop of the assembly dimension chain affects the manufacturing dimension of each part. Thats why, the assembly accuracy constraints are generated (Sun et al , 2018).…”
Section: Precision Constraintsmentioning
confidence: 99%
“…The tolerance of the closed-loop of the assembly dimension chain affects the manufacturing dimension of each part. Thats why, the assembly accuracy constraints are generated (Sun et al , 2018).…”
Section: Precision Constraintsmentioning
confidence: 99%
“…These modeling and analysis methods provide a rich theoretical basis for the prediction of system assembly accuracy and the comprehensive analysis of tolerance. Based on the SDT theory and homogeneous coordinate transformation theory, Sun et al revealed the influence mechanism of assembly deformation on the overall assembly accuracy of mechanical system [14][15][16]. Some scholars have proposed the theoretical model and method of deviation accumulation control on the assembly path of rotor system [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Some scholars have also focused on the economic benefits associated with robot design. Sun et al (2018) proposed an assembly precision-cost model and analyzed it with a horizontal machining center as an example, which reduced the cost by 16.83% while satisfying the assembly precision. Miah et al (2022) analyze the tolerance allocation for the step difference between the aircraft cabin door and the outer skin of the fuselage.…”
Section: Introductionmentioning
confidence: 99%